SARS-CoV-2 Early Screening at the Point of Entry: Travelers From Bangladesh to Italy–July 2020 - Rueca, Martina; Di Caro, Antonino; Gruber, Cesare Ernesto Maria; Messina, Francesco; Giombini, Emanuela; Valli, Maria Beatrice; Lalle, Eleonora; Lanini, Simone; Vairo, Francesco; Capobianchi, Maria Rosaria; Bartolini, Barbara (Frontiers in Genetics, 2021)
We report phylogenetic and mutational analysis by NGS of six SARS-CoV-2 strains from patients flying from Bangladesh to Italy (July 2020). Data suggest that no further circulation of such imported strains occurred in Italy, stating the efficacy of early screening at the point of entry and supporting the importance of molecular epidemiology in monitoring the efficacy of control measures.